VY anoplasty for ectropion of anal mucosa in an adult with anorectal malformation - Enrico La Pergola; Francesco Fascetti Leon; Franco Bassetto; Paola Midrio; Piergiorgio Gamba (Elsevier, 2019)
Ectropion of anal mucosa (AME) is a possible complication following anorectal surgery and it is often cause of symptoms such as soiling, pain and bleeding affecting the patients' quality of life. Two-flaps anoplasty has been previously described for the correction of AME. We herein report a case of an adult patient who underwent a successful double V/Y-flaps for mucosal ectropion as consequence of repair of anorectal malformation (ARM).A 25 year-old woman with history of ARM presented with an extensive AME causing bleeding, pain, soiling, and dyspareunia. This condition prevented her from an effective rectal nursing and a satisfactory social life.The patient underwent the resection of ectopic mucosa and the creation of two V-shaped skin flaps to cover the skin gap. A minor dehiscence of one of the flaps was treated conservatively. At two years follow up the patient is symptoms free, has a good quality of life and can perform an effective bowel management.AME is a possible complication after anorectal surgery for ARM and the multiple V-Y plasty is a viable procedure for its treatment. A multidisciplinary approach in these cases is recommended.Level of Evidence V. Keywords: Anorectal malformation, Anoplasty, V-Y flaps, Mucosal ectropion